Pattern of Prostate Cancer in Karbala Province of Iraq: Data from Developing Country - Mjali, Ahmed; Fatah Agha, Riyad Taha Mohammed; Al-Shammari, Haider Hasan Jaleel; Alwakeel, Afnan Fouad; Sedeeq, Alaa Othman; Abbas, Nareen Tawfeeq; Kareem, Mohammed Hadi; Al-Rubai, Ali Tahseen Ali (Asian Pacific Journal of Cancer Care, 2025)
Background: Global patterns of prostate cancer differ with respect to environmental and demographic factors. Objective: Our study’s objective was to evaluate the prostate cancer pattern in Karbala province of Iraq, make comparisons with other populations to detect potential changes. Methods: A retrospective descriptive research was conducted at Al-Hussein Cancer Center in Karbala, Iraq, on 265 patients found to have prostate cancer from January 2012 to December 2020 with assessment of age, presenting symptoms, pathological characteristics and stage. Results: Median age was 70 years. The most common symptoms were irritative symptoms in 58.11% of patients, the most frequent histopathology was adenocarcinoma in 95.85% of patients, A prostate-specific antigen level (PSA) was > 20 ng/ml in more than 56% of patients. The Gleason score was ≥7 in (86.22%) of adenosarcomas patients. Unfortunately, more than half of our patients (51.32%) presented as stage IV. Conclusion: This is the first statistical research about prostate cancer in Karbala province of Iraq. It can be used as a starting point to examine epidemiological characteristics, evaluate current developments, and develop therapeutic strategies.